Identification of Gastrointestinal Microbiota in Hawaiian Green Turtles (Chelonia mydas). (April 2020) - McDermid, Karla J; Kittle, Ronald P; Veillet, Anne; Plouviez, Sophie; Muehlstein, Lisa; Balazs, George H
Green turtles ( Chelonia mydas ) have a hindgut fermentation digestive tract, which uses cellulolytic microbes to break down plant matter in the cecum and proximal colon. Previous studies on bacterial communities of green turtles have not identified in situ hindgut microbiota, and never before in Hawaiian green turtles, which comprise an isolated metapopulation. Fresh samples using sterile swabs were taken from five locations along the gastrointestinal tracts of eight green turtles that had required euthanization. Bacteria were cultured, aerobically and anaerobically, on nutrient agar and four differential and selective media. Samples at three sections along the gastrointestinal tracts of two green turtles were analyzed using 16S metagenomics on an Ion Torrent Personal Genome Machine. More than half of the 4 532 104 sequences belonged to the phylum Firmicutes, followed by Bacteroidetes and Proteobacteria, which are characteristic of herbivore gut microbiota. Some microbiota variation existed between turtles and among gastrointestinal sections. The 16S sequence analysis provided a better representation of the total gastrointestinal bacterial community, much of which cannot be cultured using traditional microbial techniques. These metagenomic analyses serve as a foundation for a better understanding of the microbiome of green turtles in the Hawaiian Islands and elsewhere.